2015
DOI: 10.1038/jid.2014.456
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Betapapillomavirus Antibodies around Transplantation Predicts the Development of Keratinocyte Carcinoma in Organ Transplant Recipients: A Cohort Study

Abstract: Organ transplant recipients (OTRs) have an increased risk of developing keratinocyte carcinomas (KCs). The aim of this study was to correlate infection with human papillomaviruses (HPVs) belonging to the beta genus (Beta-papillomavirus (Beta-PV)) at transplantation with later development of KCs. In a cohort study, sera collected between 1 year before and 1 year after transplantation of OTRs transplanted between 1990 and 2006 were tested for antibody responses against the L1 capsid antigen of Beta-PV and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 44 publications
1
30
0
3
Order By: Relevance
“…Earlier critical viral activities are not excluded by seronegativity. It is highly interesting that beta HPV seropositivity around transplantation implied a hazard ratio of 2.8 to develop KC in organ transplant recipients, who were followed for up to 22 years (Genders et al, 2014). …”
Section: Epidemiology Of Beta Hpv Infectionsmentioning
confidence: 99%
“…Earlier critical viral activities are not excluded by seronegativity. It is highly interesting that beta HPV seropositivity around transplantation implied a hazard ratio of 2.8 to develop KC in organ transplant recipients, who were followed for up to 22 years (Genders et al, 2014). …”
Section: Epidemiology Of Beta Hpv Infectionsmentioning
confidence: 99%
“…Case‐control studies in both OTR and immunocompetent populations have shown that the presence of βPV DNA or antibodies was associated with a 1.5‐ to 3‐fold increased risk of cSCC 12, 20, 21, 22, 23, 24, 25, 26, 29, 31, 32. It was not possible, however, to determine whether the βPV infection increases risk of cSCC development or whether cSCC formation promotes active proliferation of βPV.…”
Section: Introductionmentioning
confidence: 99%
“…It was not possible, however, to determine whether the βPV infection increases risk of cSCC development or whether cSCC formation promotes active proliferation of βPV. To our best knowledge, there is only 1 published cohort study in OTRs that investigated the influence of βPV infection on the development of cSCC 26. In a single‐center study in 445 patients, OTRs who were βPV seropositive around the time of transplantation had an almost 3‐fold increased risk of developing cSCC during the 22‐year follow‐up period 26.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous β-HPVs are associated with SCCs in patients with the autosomal recessive disorder epidermodysplasia verruciformis (EV) (Gewirtzman et al, 2008). The burden of β-HPV infection predicts risk of subsequent development of SCC (Farzan et al, 2013), and antibodies to β-HPVs, suggesting active HPV infection, are associated with SCC in immunosuppressed patients (Genders et al, 2015). However, transcription of β-HPV RNA is not observed in healthy skin or in premalignant or malignant skin lesions (Arron et al, 2011), supporting a 'hit-and-run' role for β-HPVs in cutaneous carcinogenesis (Pfister, 2003).…”
Section: Introductionmentioning
confidence: 99%